Assessment of School Assessors’ Knowledge and Competence on Diagnostic Overshadowing for Appropriate Placement of Children with Intellectual Disability in Cross River State, Nigeria - Orim, Samuel Orim; Orim, Matthew Ashike; Alawa, David Adie; Olayi, James Eburikuri; Ewa, James Abua; Essien, Essien Ekpenyong; Essien, Cecilia Kori; Olofu, Martin Afen; Igba, Innocent Ushi; Unimke, Sylvester Akongi; Osaji, Nsagha Nkang; Ogar, Raymond Ogbebe; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
This study assessed the knowledge and competence of special teachers and psychologists in diagnostic overshadowing and differential diagnosis in children with intellectual disability in Cross River State, Nigeria. A descriptive research design was adopted. Sixty (60) respondents comprising teachers and school psychologists were purposively selected from three main special schools in Cross River State. Two research questions were raised to guide the study. A rating scale titled ‘Mental Health Diagnosis Competency Scale (r=0.91)’ was used for data collection. The instrument was used to assess the knowledge and competence of special teachers and school psychologists in diagnostic overshadowing and differential diagnosis in children with intellectual disabilities. The data collected were statistically analyzed using percentages, frequency count, and bar chart. The findings revealed that most teachers and school psychologists have no knowledge of psychiatric symptomatology in children with intellectual disabilities. Respondents also lack adequate competence in differential diagnosis, leading to wrong special education placement and inadequate intervention plans for such children. It was recommended, among others, that the government provide in-service training for teachers and psychologists to equip them on current issues and practices in special education, such as differential diagnosis and collaborative partnership within a transdisciplinary approach.